Pengaruh Kebijakan Dividen, Leverage, Dan Profitabilitas Terhadap Nilai Perusahaan - Serafina, Ligia; Yuliati, Anik; Kirana, Nanda Wahyu Indah (Gorontalo Accounting Journal, 2025)
This study aims to examine the influence of dividend policy, leverage, and profitability on firm value. The research employs a quantitative approach. The population includes companies in the consumer non-cyclical Â sector listed on the Indonesia Stock Exchange during the period from 2021 to 2023. The sample comprises 123 data points derived from 41 companies over a 3-year period, selected using purposive sampling techniques. The data analysis technique applied is panel data regression analysis. The findings indicate that dividend policy, as measured by the Dividend Payout Ratio (DPR), and profitability, as measured by Return on Assets (ROA), do not have an impact on firm value. Conversely, leverage, as measured by the Debt to Equity Ratio (DER), has a significant positive impact on firm value.